YOUTH UNEMPLOYMENT: IMPLEMENTATION OF YOUTH MUST WORK PROGRAMME IN IMO STATE NIGERIA, 2011-2015 - ONYEMAECHI UGWUIBE, Ph.D, CHRISTOPHER; N. ONAH, Ph.D , FRANCISCA; MICHAEL, OGANA,; O. ONAH, Ph.D, FAB. (International Journal of Psychosocial Rehabilitation, 2021)
The study examined youth unemployment with a specific focus on implementation of youth must work programs in Imo State, Nigeria, 2011-2015. The study drew on survey data from a sample of 174 respondents within the study areas. Using the Normalization Process Theory (NPT), the paper is of the view that the implementation of youth must work programs and youth unemployment in Imo State is an intervention program initiated by the government of Imo State to reduce the high rate of youth unemployment in the state. A five-point Likert scale was used in the analysis. The chi-square at the appropriate level of confidence (0.05) was used for the research hypotheses. Data for the study were gathered through primary and secondary sources. The findings revealed, among others, that youth must work programs have failed to make adequate provision for engaging the youth and are therefore unable to resolve the development disaster facing the state. Also, the implementation of the program made minimal impact on the living conditions and standard of living of the people, so in spite of the effort and financial input by the state government, youth unemployment is still on the increase. The paper recommended, among others, that the government should try and monitor all allocation meant for the program to avoid making it insufficient for the targeted beneficiaries.